Integrating firefly algorithm in artificial neural network models for accurate software cost predictions. Issue 8 (8th June 2016) - Kaushik, Anupama; Tayal, Devendra Kr.; Yadav, Kalpana; Kaur, Arvinder
Abstract: Human effort is one of the main resources of software cost estimation. A successful software project development primarily relies on accurate effort prediction at an early stage of development. There are many effort prediction models in the literature. Deciding which model to choose is a challenge for the project managers. This paper investigates whether it is possible to improve the accuracy of software cost estimations by coupling firefly algorithm with the existing artificial neural network (ANN) models used in software cost predictions. The firefly algorithm is one of the recent evolutionary computing models inspired by the behaviour of fireflies in nature. This is compared with particle swarm optimization used already in literature for software cost estimations. The ANN models examined in this work include radial basis function network and functional link artificial neural networks models. The experimental results show that ANN models perform extremely well by incorporating firefly algorithm and intuitionistic fuzzy C‐means for data preprocessing. The proposed approach is empirically validated through a statistical framework. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : This paper aims to improve the software cost estimations by embedding firefly algorithm with the existing artificial neural network models used in software cost predictions. The artificial neural network models examined in this work include redial basis function network and functional link artificial neural networks models. The block diagram for firefly algorithm‐functional link artificial neural networks is shown in the figure.